2011
DOI: 10.1093/brain/awq378
|View full text |Cite
|
Sign up to set email alerts
|

The long-term risk of premature mortality in people with epilepsy

Abstract: People with epilepsy have an increased risk of premature death. The risk is highest soon after onset of seizures. We report the findings of a long-term follow-up population-based study of people with epilepsy with regards to premature mortality. The National General Practice Study of Epilepsy is a prospective study flagged at the National Health Service Information Centre in the UK. Over 1000 people with new onset seizures were followed from the mid 1980s until April 2009. Of these, 564 people were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
179
2
25

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(225 citation statements)
references
References 37 publications
19
179
2
25
Order By: Relevance
“…The problem of premature deaths has been a burning issue for many years and focused attention of researchers both in Poland [52,53] and abroad [54][55][56][57][58][59][60][61]. Many authors point out that the level of the health status and mortality is different for different regions of Poland.…”
Section: Determinants Of Premature Mortality In a City Population O Rmentioning
confidence: 99%
“…The problem of premature deaths has been a burning issue for many years and focused attention of researchers both in Poland [52,53] and abroad [54][55][56][57][58][59][60][61]. Many authors point out that the level of the health status and mortality is different for different regions of Poland.…”
Section: Determinants Of Premature Mortality In a City Population O Rmentioning
confidence: 99%
“…Noen blir mobbet eller stigmatisert. Det er også 5 -6 ganger økt risiko for plutselig anfallsrelatert død (8,9). I tillegg er det en betydelig psykiatrisk komorbiditet i denne pasientgruppen (10).…”
Section: Hvorfor Tidlig Kirurgisk Intervensjon?unclassified
“…It has been estimated that 65 million people live with epilepsy worldwide [2]. Long-term, population based, prospective studies have shown an increased risk of premature mortality in patients with epilepsy by more than twice that of the general population [3][4][5]. The higher proportion of deaths in the epilepsy cohort is due to many aetiologies including malignant neoplasms, pneumonia and other respiratory diseases, cerebrovascular diseases and cardiovascular diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term, population based, prospective studies have shown an increased risk of premature mortality in patients with epilepsy by more than twice that of the general population [3][4][5]. The higher proportion of deaths in the epilepsy cohort is due to many aetiologies including malignant neoplasms, pneumonia and other respiratory diseases, cerebrovascular diseases and cardiovascular diseases [4,5]. Causes of mortality as a direct consequence of seizures and epilepsy include sudden unexpected death in epilepsy (SUDEP), accidental deaths due to epileptic seizures and deaths from status epilepticus.…”
Section: Introductionmentioning
confidence: 99%